Exercise in the heat: Effect of fluid ingestion on blood-brain barrier permeability - Watson, P.; Black, K. E.; Clark, S. C.; Maughan, R. J. (Medicine & Science in Sports & Exercise, 2006)
Introduction: This study examined changes in serum S100[beta] concentration, a peripheral marker of BBB permeability, in response to exercise in the heat with and without fluid ingestion.